Design and development of PWM switching for 5-level multiphase interleaved DC/DC boost converter using FPGA - A. F. H. A. Gani; A. A. Bakar; A. Ponniran; M. Hussainar; M. A. N. Amran (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The continuously increasing demand for control on electric power equipment has led to the rapid technological development in various applications such as renewable energy, electric drives, and communication. Pulse Width Modulation (PWM) switching is an important technique to control the output voltage. PWM signals can either be generated using digital controller or analog controller. Digital controllers are widely used to generate PWM signals due to their reliability in solving complex algorithms within short amount of time. Multiphase boost converter is capable to overcome high input current ripple, current stress and semiconductor losses in conventional boost converter. This paper proposes a PWM switching scheme for multiphase interleaved converter using Field Programmable Gate Array (FPGA). The proposed switching scheme uses PWM switching technique that is implemented by programming Altera DE2-70 board. The duty cycle can be easily adjusted using assigned switches on the Altera board. For validation, switching frequency was set to 100 kHz, and then switching signal was observed using oscilloscope.